Subject and Abject: TikTok as a Playing Space in Constructing Self-Identity for Women in the Digital Era - Kurniawati, Juliana; Sudahri, Ari (Jogjakarta Communication Conference (JCC), 2025)
This article examines the role of TikTok as a playing space in relation to women's identity construction, focusing on the concept of "subject" and "abjects" inspired by Julia Kristeva's thinking. TikTok is an increasingly popular social media platform, not only a medium for creative expression, but also a dynamic space where women negotiate, construct and deconstruct their identities through the content they produce and consume. They utilize platform features, such as challenges, filters, and trends, to shape and display their identities. This article uses netnography methods to analyze digital cultural practices on TikTok. Observing female users interacting, creating, and responding to content related to self-identity. Data were collected through participant observation of activities on the platform, analysis of video content, and comments that emerged, to understand the dynamics of identity formation in a digital context. The research findings reveal that TikTok functions as a liminal space where the boundaries between "subjects" (identities that display their selfhood) and "abjects" (identities that are rejected or considered taboo) become blurred or fluid, allowing women to explore complex aspects of themselves that are often marginalized in traditional social contexts. Women as active subjects, produce content for their own pleasure, not to please the male gaze, but this becomes problematic when they follow the logic of the media in presenting themselves. This article makes a significant contribution to the understanding of the dynamics of gender identity construction in the digital era, as well as the implications of social media as a play space that facilitates the construction of self-identity.